PERAN GURU PENDIDIKAN AGAMA ISLAM SEBAGAI FASILITATOR DALAM MENGEMBANGKAN SOFT SKILLS SISWA - Faizatul Widat; Rohmatum Mazidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to find out the role of Islamic Religious Education teachers as facilitators in developing soft skills of students in class X of MA Riyadlus Sholihin social studies program which totals 15 students. This study uses a qualitative approach with a descriptive type of research. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing to obtain a clear picture of the role of teachers in the learning process. The results of the study show that Islamic Religious Education teachers have tried to carry out their role as facilitators through the application of interactive learning methods such as group discussions, questions and answers, and presentations. These efforts have a positive impact on increasing student participation, although there are still some students who tend to be passive and lack confidence in expressing opinions. Students' soft skills such as communication skills, cooperation, and confidence are still in the medium category, but are beginning to develop gradually. Supporting factors in the development of students' soft skills include teachers' efforts in creating active learning and the willingness of some students to participate. The inhibiting factors include the dominance of the lecture method, low student confidence, and passive learning habits. Therefore, continuous efforts are needed from teachers in implementing varied and participatory learning strategies so that the development of students' soft skills can run optimally.